1964
DOI: 10.1042/bj0930641
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of glucose uptake by muscle. 7. Effects of fatty acids, ketone bodies and pyruvate, and of alloxan-diabetes, starvation, hypophysectomy and adrenalectomy, on the concentrations of hexose phosphates, nucleotides and inorganic phosphate in perfused rat heart

Abstract: Newsholme & Randle (1961) found that the concentrations of glucose 6-phosphate and fructose 6-phosphate were decreased and that of fructose * Part 6: Newsholme & Randle (1962).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
1
1

Year Published

1979
1979
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(45 citation statements)
references
References 13 publications
0
43
1
1
Order By: Relevance
“…Thus increased plasma NEFA enhanced muscle glycogen deposition during the low-dose insulin clamp, an effect also seen in the heart (Table 4). Previous studies [15,20,39] have shown that enhanced glycogen synthesis in heart and red skeletal muscle when lipid oxidation is increased is associated with an increase in tissue glucose-6-phosphate secondary to inhibition of glycolysis at the level of phosphofructokinase [15,39,40]. Although we did not measure glucose-6-phosphate concentrations, increased muscle glycogen deposition but unchanged glucose turnover at low-dose insulin is consistent with an inhibition of glycolytic flux by increased fatty acid availability.…”
Section: ]mentioning
confidence: 51%
“…Thus increased plasma NEFA enhanced muscle glycogen deposition during the low-dose insulin clamp, an effect also seen in the heart (Table 4). Previous studies [15,20,39] have shown that enhanced glycogen synthesis in heart and red skeletal muscle when lipid oxidation is increased is associated with an increase in tissue glucose-6-phosphate secondary to inhibition of glycolysis at the level of phosphofructokinase [15,39,40]. Although we did not measure glucose-6-phosphate concentrations, increased muscle glycogen deposition but unchanged glucose turnover at low-dose insulin is consistent with an inhibition of glycolytic flux by increased fatty acid availability.…”
Section: ]mentioning
confidence: 51%
“…During increased cardiac power we observed that diabetic pigs have decreased PDH activity and lactate uptake and enhanced ␤-hydroxybutyrate uptake compared with healthy animals (19). It is generally postulated that impaired pyruvate oxidation in the diabetic heart is partially due to an increase in mitochondrial NADH/NAD ϩ (19,32,33,40); however, evidence for this is lacking due to the inability to measure mitochondrial NADH and NAD ϩ in the intact heart. The overall goal of the present study was to 1) assess the role of parallel activation of multiple metabolic steps in the regulation of cytosolic and mitochondrial NADH/NAD ϩ during the dynamic transition from resting conditions to high rates of cardiac energy expenditure, as observed with exercise; 2) investigate the effects of elevated arterial lactate concentration on mitochondrial pyruvate and fatty acid oxidation and the cytosolic and mitochondrial NADH/NAD ϩ ratios; and 3) determine whether impaired pyruvate oxidation under diabetic conditions requires an increase in mitochondrial NADH/ NAD ϩ .…”
mentioning
confidence: 80%
“…The overall effect of activated AMPK is to increase ATP supply by accelerating the rates of fatty acid oxidation and glycolysis. However, high rates of fatty acid oxidation dramatically inhibit glucose oxidation rates via the Randle cycle (102). That is, fatty acid-derived acetyl CoA is able to decrease the production of glucose-derived acetyl CoA via inhibition of the pyruvate dehydrogenase complex (66).…”
Section: Regulation Of Myocardial Energy Utilizationmentioning
confidence: 99%